(untitled) (Società e diritti, 2016)
The Italian bureaucracy is afflicted by many evils. The author highlights the dysfunctional effects of many factors: from corruption to cronyism, from informal organigrams to the influence of political cultures. Through a historical excursus the bureaucracy of our country seems to have been characterized by inefficiency; it is a place of occupation of political parties and broth of local, family and subversive powers of constitutional values. Key words: Bureaucracy, Cronyism,Corruption